El buglere: lengua obsolescente - Quesada, J. Diego (2008)
El estudio plantea una caracterización general del buglere, dialecto del bocotá, perteneciente a la familia chibcha. Se aportan algunos datos de orden social y cultural asociados a la diáspora de la etnia, y posteriormente se centra en la caracterización tipológica de la lengua, que la vincula directamente con la familia mencionada. Señala su autor que el notable riesgo de extinción obliga a llevar a cabo estudios descriptivos sistemáticos y sostenidos, con la esperanza de propiciar su eventual revitalización. This study presents a general characterization of Buglere –a dialect of Bocotá, which belongs to the Chibcha family. It provides information on the social and cultural system related to the scattering of that ethnic group. Attention is then given to the typological characterization of the language, in which it is linked directly to the family mentioned. The author affirms that the significant risk of extinction is what leads to systematic, sustained descriptive studies, with the hope of eventually revitalizing the language.